The impact of social activity on cardiovascular disease risk among middle-aged and older adults in China: a nationwide cohort study based on the CHARLS database - Wu, Yingting; Cheng, Qi; Song, Haiyang; Gong, Xinyue; Wang, Sihan; Xu, Kehui; Qin, Lei; Cheng, Jing; He, Fei (Frontiers in Public Health, 2025)
ObjectiveThis study aims to examine the relationship between social activity and the risk of cardiovascular disease (CVD) in middle-aged and older adults in China.MethodsWe used data from the China Health and Retirement Longitudinal Study (CHARLS) collected between 2011 and 2020. The study followed 4,099 participants aged 45 and older, all free from cardiovascular disease at baseline (2011), over a 9-year period. CVD status was self-reported by participants. Kaplan–Meier survival curves were employed to illustrate the cumulative incidence of cardiovascular events across different levels of social activity. Cox proportional hazards regression models and restricted cubic spline (RCS) were used to evaluate the association between social activity and CVD risk. Subgroup analyses were conducted to explore potential interactions between social activity and CVD risk, stratified by age, gender, education level, smoking and drinking status, number of chronic conditions, depression, and body mass index (BMI).ResultsA total of 4,099 participants were included in the analysis. Over the 9-year follow-up period, 813 cardiovascular events occurred. After adjusting for age, gender, residence, education, marital status, smoking and drinking habits, chronic disease burden, depression, and BMI, each 0.1 decrease in social activity level was associated with a 7.4% increased risk of cardiovascular events (aHR, 1.074; 95% CI: 1.069–1.079).ConclusionSocial activity is significantly linked to the risk of cardiovascular disease among middle-aged and older adults in China. These findings emphasize the importance of maintaining social engagement to support cardiovascular health in this population.